SOURCES OF BOOK HISTORY - KAUNAS, DOMAS (Knygotyra, 2010)
Investigation of book history sources or source research is a book science discipline that investigates the origin of book history sources, their retrieval, classification, evaluation and usage. This is partly a theoretical and partly an applied discipline. The theoretical part of source investigation includes the analysis of the authenticity, reliability, and typology of sources. The applied part of source investigation focuses on the issues of building the basis of sources and their usage. The general solution in the methodology of processing sources is classification. The main concepts of classification are type and sort. A type is perceived as a model of a group of objects (data, work or things) having a general essential property. A sort is defined as an object under classification that meets the type definition by a general or a partial attribute.Scholars of different countries have agreed that a type is determined by the following attributes: 1) time of origin (primary and secondary), 2) information format (written, visual, audial, linguistic, or objects). Book history perceives the second attribute as the most important because, according to it, sources are defined as written and non-written. Written sources are most numerous; depending on their purpose they are grouped into the following sorts: 1) books; 2) official documents; 3) critical and evaluation materials; 4) bibliographies; 5) statistical documents; 6) reference books of institutions and companies, catalogues, address books; 7) archival clerical documents; 8) advertisements of publications; 9) information material of periodicals; 10) diaries; 11) correspondence; 12) memoirs; 13) book research in othersciences; 14) publicistic writings; 15) book ownership marks; 16) other manuscript or printed sources.Non-written sources are less diverse. They include: 1) visual and audial documents; 2) objects of material culture (buildings, equipment, memorials, book culture means). Critical evaluation concerns mainly written sources. It may be internal and external. The first one helps to identify the sort of a source as a document and its attributes, and the latter is related to the significance of a document. A researcher builds his conclusions on the totality of sources and reconstructs the facts and phenomena that belong to the past of a book and serve as a basis for determining the regularities of its development.
Keywords: ...